2021
DOI: 10.1007/s00262-021-02998-1
|View full text |Cite
|
Sign up to set email alerts
|

Small cell lung cancer stem cells display mesenchymal properties and exploit immune checkpoint pathways in activated cytotoxic T lymphocytes

Abstract: Small cell lung cancer (SCLC) is an aggressive tumor type with early dissemination and distant metastasis capacity. Even though optimal chemotherapy responses are observed initially in many patients, therapy resistance is almost inevitable. Accordingly, SCLC has been regarded as an archetype for cancer stem cell (CSC) dynamics. To determine the immune-modulatory influence of CSC in SCLC, this study focused on the characterization of CD44+CD90+ CSC-like subpopulations in SCLC. These cells displayed mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
(74 reference statements)
3
15
0
Order By: Relevance
“…On the other hand, CD44 is a necessary protein for EMT, 5–9 and EMT has been associated with a broad inflammatory microenvironment characterized by coexistent upregulation of co-stimulatory and co-inhibitory checkpoint molecules in human lung cancer. 24 29–31 We also observed that intratumoral regions with elevated tumor cell CD44 had prominent upregulation of co-inhibitory (TIM-3, B7-H3, PD-L1) and co-stimulatory (ICOS, CD40, CD27) molecules in two independent NSCLC cohorts. Of note, although EMT has been generally associated with poorer outcomes and treatment resistance in several cancers, 6 7 some tumor types with more mesenchymal features such as sarcomatoid malignant pleural mesotheliomas 32 or certain subtypes of small cell lung cancers (SCLC), 33 also display an inflammatory microenvironment and show higher sensitivity to checkpoint blockade therapies.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…On the other hand, CD44 is a necessary protein for EMT, 5–9 and EMT has been associated with a broad inflammatory microenvironment characterized by coexistent upregulation of co-stimulatory and co-inhibitory checkpoint molecules in human lung cancer. 24 29–31 We also observed that intratumoral regions with elevated tumor cell CD44 had prominent upregulation of co-inhibitory (TIM-3, B7-H3, PD-L1) and co-stimulatory (ICOS, CD40, CD27) molecules in two independent NSCLC cohorts. Of note, although EMT has been generally associated with poorer outcomes and treatment resistance in several cancers, 6 7 some tumor types with more mesenchymal features such as sarcomatoid malignant pleural mesotheliomas 32 or certain subtypes of small cell lung cancers (SCLC), 33 also display an inflammatory microenvironment and show higher sensitivity to checkpoint blockade therapies.…”
Section: Discussionsupporting
confidence: 56%
“…It is a surface marker commonly overexpressed by tumor cells with cancer initiating properties, 6 7 20 and has therefore been repeatedly associated with cancer stem cells particularly in breast cancer. [20][21][22][23][24] To our knowledge, the association between tumor cell CD44 overexpression and improved clinical outcomes to PD-1 axis blockade has not been previously reported. In the present study, we have performed rigorous validation of this novel finding, including orthogonal biomarker assessment with a second QIF-based technology (with prior validation of an anti-CD44 antibody following recommended guidelines 16 ), and external validation utilizing whole tissue sections by independent investigators.…”
Section: Discussionmentioning
confidence: 85%
“…Second, small cell lung carcinomas are associated with the lack of PD-L1 immunosuppressive barrier allowing the immune cell infiltration, but with high expression of desmosomes disassembly barrier, both facilitators of distant metastasis and shorter overall patient survival, otherwise be targeted effectively with immunotherapy PD-L1 expression. Third, the high levels of EMT transcriptions factors expressed by SCLC cells can confer mesenchymal properties, on the one hand justifying its histologic fusiform pattern, and on the other hand the acquisition of immune regulatory capacities for checkpoint blockade immunotherapy, as recently demonstrated in an elegant work made by Kursunel and colleagues (14).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, normal lung contains a population of neuroendocrine cells (NE), referred as Kulchitsky cell, within the bronchial tree and neuroendocrine bodies in the periphery, which also might give rise to carcinoids, a specific group of tumors based on their secretory products, distinct staining characteristics, and ability to uptake and decarboxylate amine precursors (11). In contrast, SCLC do not arise from Kulchitzky cells, but from multipotent or undifferentiated neuroendocrine NE cells in the central bronchial tree (12)(13)(14) as previously demonstrated in experimental models genetically modified (15). Given these unusual characteristics of PNENs, not only is it still often difficult to oncologist predicts which tumors will invade, metastasize, and abbreviate the patient's life, nevertheless, effective adjuvant treatments still depend on identifying these tumors shortly after biopsy or surgery as well.…”
Section: Introductionmentioning
confidence: 99%
“… 57 Compared with epithelial cancer cells, mesenchymal cancer cells are less responsive to anti‐cytotoxic lymphocyte‐associated protein 4 (CTLA4) immunotherapy. 59 In addition, the expressions of programmed death ligand‐1 (PD‐L1), PD‐L2, and B7 homolog 3 (B7‐H3) are up‐regulated in tumor cells that have undergone EMT, which can facilitate the immune escape of cancer cells. 58 , 60 …”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%